Trypanosoma cruzi serinecarboxipeptidase is a sulfated glycoprotein and a minor antigen in human Chagas disease infection - Soprano, Luciana L (2018)
Fil: Soprano, Luciana L ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.